2021
DOI: 10.3390/ph14101052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Computational Analysis, and Antiproliferative Activity of Novel Benzimidazole Acrylonitriles as Tubulin Polymerization Inhibitors: Part 2

Abstract: We used classical linear and microwave-assisted synthesis methods to prepare novel N-substituted, benzimidazole-derived acrylonitriles with antiproliferative activity against several cancer cells in vitro. The most potent systems showed pronounced activity against all tested hematological cancer cell lines, with favorable selectivity towards normal cells. The selection of lead compounds was also tested in vitro for tubulin polymerization inhibition as a possible mechanism of biological action. A combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…For a more beneficial effect, the additional pendant aromatic ring should be 2-naphthyl or para -substituted phenyl. Especially advantageous was the introduction of a dimethylamine moiety, which was consistent with literature data [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…For a more beneficial effect, the additional pendant aromatic ring should be 2-naphthyl or para -substituted phenyl. Especially advantageous was the introduction of a dimethylamine moiety, which was consistent with literature data [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 86%
“…Recently, it has been reported that the introduction of an alkyl or aryl group at position N 1 of benzimidazole-derived acrylonitriles can result in promising antiproliferative agents [ 45 , 46 ]. Therefore, to explore the structure–activity relationships of the synthesized 2-(1 H -indol-2-yl)-3-acrylonitriles in more detail, we turned our attention to their N -substituted analogs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the obtained trajectory results were further analyzed using the ptraj module of the Amber package. 34…”
Section: Methodsmentioning
confidence: 99%